PENERAPAN KOMPONEN TEKNOLOGI PRODUKSI DALAM SISTEM BUDIDAYA TERHADAP PRODUKTIVITAS PADI BERAS MERAH DI KECAMATAN SEMANU KABUPATEN GUNUNGKIDUL - Endang Widayati (Universitas Pahlawan Tuanku Tambusai, 2022)
The potential for dry land agriculture in Indonesia is very large, the area of ​​dry land in Indonesia reaches 9.7 million hectares. However, there are many problems in dry land farming systems, including the problem of marginal land with limited water availability, the underdeveloped cultivation technology, the limited variety of suitable plants, and the low income of farmers. The aims of the research are (1) to determine the intensity of the application of production technology components (basic and optional components) in the brown rice cultivation system and their effect on productivity (2) to identify the factors that influence the intensity of the application of these technological components. The basic method used is descriptive and explanative analysis methods. Determination of the sample of brown rice farmers (respondents) as many as 60 people was carried out by simple random sampling technique. The analytical method used in this study is the proportion test and the Chi-Square test. The results showed that (1) the application of intensive basic technology components was 68.33% and 31.67% which were not yet intensive. As for the selected technology component, which is intensive is 71.67% and which is not yet intensive is 28.33%. (2) Farmers' intensity in applying technology components can be influenced by factors of land area, farmer's age, level of education and counseling. By applying the components of production technology in the brown rice cultivation system, productivity can be increased. Keywords: Production Technology Components, Cultivation Systems, Productivity